P84 Advanced stage and aggressive cancers form a considerable proportion of lung malignancies in idiopathic pulmonary fibrosis and scleroderma-associated ILD. (December 2018) - Ratnakumar, S; Madani, Y; Aboelhassan, S; Kemp, S; George, P; Wells, AU; Renzoni, E; Kokosi, M; Margaritopoulos, G; Kouranos, V; Devaraj, A; Desai, S; et al.
Abstract : Background: Studies using public health records have reported an increased risk of developing lung cancer in patients with interstitial lung disease (ILD). However little information exists on the frequency of lung cancer in UK ILD practice. Method: All cases discussed in the Royal Brompton Hospital Lung Cancer MDT meetings between May 2015 and April 2018 were interrogated for referring indication, patient attributes, staging and cancer confirmation. Results: 74 ILD patients (45 male) and 223 COPD patients (132 male) were identified; median age at cancer diagnosis (70) was similar in both groups. 'Ever' smokers formed three-quarters (55/74) of the ILD group. 1 in 4 ILD patients had IPF. Cancer was pathologically proven in 25/74 (33.8%) of ILD patients, against 56/223 (25.1%) of those with COPD. Cancer that was suspected due to CT morphology or progression but were not amenable to sampling because of poor fitness, inaccessibility or metastatic disease occurred in 15/74 (20.3%) and 22/223 (9.9%) of ILD and COPD patients respectively (p<0.01). As a category, [proven+suspected] cancers were more common in ILD (p<0.002). The proportion of stage IV non-small cell lung cancer (NSCLC) was also higher in ILD (8/18, 44.4%) than in COPD (10/45, 22.2%) (p=0.04). Small cell lung cancer (SCLC) was proven in 16% (4/25) and 7.1% (4/56) of ILD and COPD patients respectively. The four cases of SCLC in the ILD group occurred in patients with radiologic evidence of UIP (3 cases of IPF and one case of combined emphysema and UIP-pattern fibrosis). Within the IPF subgroup, 4 also developed stage IV NSCLC. Scleroderma with ILD was the commonest connective tissue disease (5/7) in this analysis, with two patients having stage IV and one stage IIIB NSCLC. Conclusion: The risk of developing lung cancer is high amongst those with ILD especially in IPF and when there is evidence of suspicious 'interval CT' change. Stage IV NSCLC and aggressive (SCLC) are frequent in patients with IPF and scleroderma who develop lung malignancies. Delayed cancer diagnosis may result from decreased suspicion in patients who have progressive ILD or diffuse lung disease that complicates radiological interpretation.